ANALYZING THE IMPACT OF SOLAR ENERGY INVESTMENT ON SUSTAINABLE ECONOMIC DEVELOPMENT IN IRAQ (2015–2025) - Hadeel Jasim Hajim (Scholars Digest Publishing, 2025)
This research examines the impact of investment in solar energy on sustainable economic development in Iraq during the period (2015–2025), particularly in light of the challenges facing the Iraqi economy due to its heavy dependence on oil exports and the fluctuations in global oil prices. The importance of the study stems from Iraq's urgent need to diversify its energy sources and achieve sustainable development through clean and renewable alternatives—most notably solar energy, for which Iraq possesses abundant natural potential. The research problem lies in the insufficient actual utilization of solar energy in Iraq, despite the existence of scattered investment projects and a lack of adequate analytical studies to measure the impact of these investments on macroeconomic indicators such as economic growth, unemployment, and energy stability. The study aims to achieve a set of objectives, most notably: measuring the volume of solar investments, analyzing their relationship with economic growth, and assessing their contribution to job creation and energy stability. The research adopted both descriptive and quantitative analytical methodologies, using official and statistical data for the study period and analyzing it with econometric tools. The results indicated a positive relationship between solar energy investments and economic growth, as well as their contribution to reducing unemployment rates and improving the stability of the electricity grid in some provinces.The study concluded with several recommendations, most notably: strengthening the legislative framework for renewable energy investment, expanding technical training programs, and improving energy network infrastructure to ensure optimal benefit from this vital sector in supporting sustainable development in Iraq.
Keywords: Impact of investment, solar energy, sustainable development.